Efectividad de la gestión en las universidades, desde modelos de percepción de calidad de estudiantes: El modelo de la Universidad Bernardo O'Higgins - Claudio Ruff Escobar; Marcelo Ruiz Toledo; Alexis Matheu Pérez; Paola Juica Martínez; Gerardo Anabalón Arenas (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– Quality in education is a recurring theme in this society where the training of competent professionals is an essential element for their progress and development in the face of growing market demands. The competitiveness given by the multivariety of educational offerings, together with the historical role of universities as knowledge managers, drives universities to focus on a permanent process of reflection and analysis about the fulfillment of their institutional objectives and the degree of effectiveness measured in the satisfaction of their main clients, that is, their students. In this context, this research aims to establish priorities for financial and institutional management from the degree of satisfaction of university students at Bernardo O'Higgins University by applying the methodology of modeling structural equations, based on variances, seeking relationships between different areas of satisfaction, with multivariate methods factorial analysis. For these purposes, the internal consistency method based is given by the average of the correlations between the items in order to estimate the reliability of his instrument. Finally, it should be pointed out that the study has managed to model a system derived from the response behaviour of students and teachers at the Universidad Bernardo O'Higgins.
Keywords: I23; C02; 330; quality; effectiveness; evaluation; higher education; service culture; satisfaction survey